Addition of compatibilized nanoclay to GFRCs for improved izod impact strength and tensile properties. (October 2021) - Shelly, Daksh; Nanda, Tarun; Mehta, Rajeev
This research examines the effect of nanoclay silanization/compatibilization on the izod impact strength and tensile properties of epoxy-clay-based glass fiber reinforced composites (GFRCs). As per the existing literature, a key step in silanization of clay is washing of the silanized clay with acetone to remove the excess of silane molecules. However, contrary to this, the present research shows that acetone washing of the silanized clay lowers the tensile properties. GFRCs containing 2 phr nanoclay were processed. Three different montmorillonite clays were used in the initial investigations (two organically modified nanoclays designated as "CA" and "IE" and one unmodified nanoclay designated as "PG"). Silane concentration was varied in the range of 100–400% as proportion of nanoclay loading (i.e. 1X, 2X, 3X, and 4X). Silanization was validated by FTIR. XRD/TEM revealed increased d-spacing for silanized nanoclay and a partially exfoliated clay morphology in GFRCs. Highest izod impact strength (37% higher than the reference GFRC) without any loss in tensile properties was observed for GFRC reinforced with acetone washed 2X silanized "PG" nanoclay. GFRCs reinforced with silanized unwashed nanoclay (3X) showed 27% improvement in izod impact strength with significantly improved tensile strength (16% higher than the reference sample).